The risk of subsequent surgery following bowel resection for Crohn's disease in a national cohort of 19 207 patients. (6th October 2022) - King, Dominic; Coupland, Benjamin; Dosanjh, Amandeep; Cole, Andrew; Ward, Stephen; Reulen, Raoul C.; Adderley, Nicola J.; Patel, Prashant; Trudgill, Nigel
Abstract: Aim: Surgery is required for most patients with Crohn's disease (CD) and further surgery may be necessary if medical treatment fails to control disease activity. The aim of this study was to characterize the risk of, and factors associated with, further surgery following a first resection for Crohn's disease. Methods: Hospital Episode Statistics from England were examined to identify patients with CD and a first recorded bowel resection between 2007 and 2016. Multivariable logistic regression was used to examine risk factors for further resectional surgery within 5 years. Prevalence‐adjusted surgical rates for index CD surgery over the study period were calculated. Results: In total, 19 207 patients (median age 39 years, interquartile range 27–53 years; 55% women) with CD underwent a first recorded resection during the study period. 3141 (16%) underwent a further operation during the study period. The median time to further surgery was 2.4 (interquartile range 1.2–4.6) years. 3% of CD patients had further surgery within 1 year, 14% by 5 years and 23% by 10 years. Older age (≥58), index laparoscopic surgery and index elective surgery (adjusted OR 0.65, 95% CI 0.54–0.77; 0.77, 0.67–0.88; and 0.77, 0.69–0.85; respectively) were associated with a reduced risk of further surgery by 5 years. Prior surgery for perianal disease (1.60, 1.37–1.87), an extraintestinal manifestation of CD (1.51, 1.22–1.86) and index surgery in a high‐volume centre for CD surgery (1.20, 1.02–1.40) were associated with an increased risk of further surgery by 5 years. A 25% relative and 0.3% absolute reduction in prevalence‐adjusted index surgery rates for CD was observed over the study period. Conclusions: Further surgery following an index operation is common in CD. This risk was particularly seen in patients with perianal disease, extraintestinal manifestations and those who underwent index surgery in a high‐volume centre.